1979
DOI: 10.1128/aac.15.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Ampicillin Resistance in Haemophilus ducreyi

Abstract: Three of 19 strains of Haemophilus ducreyi , isolated during a recent outbreak of chancroid, were found to produce β-lactamase and to harbor a 6.0 × 10 6 -dalton plasmid. Escherichia coli transformed with this plasmid acquired β-lactamase-mediated resistance to ampicillin. The guanine-plus-cytosine content of the plasmid was found to be 41 mol%. Restriction endonuclease digestion studies suggest that a relatively large portion of the Tn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Plasmid p22209 is structurally identical to pHD747, with the exception of a complete ampicillin transppson within the latter (2). The same relationship exists between plasmids p88557 and pJB1 (2). The ampicillin transposon is not present within pHD147 (11).…”
mentioning
confidence: 77%
“…Plasmid p22209 is structurally identical to pHD747, with the exception of a complete ampicillin transppson within the latter (2). The same relationship exists between plasmids p88557 and pJB1 (2). The ampicillin transposon is not present within pHD147 (11).…”
mentioning
confidence: 77%
“…All but one strain contained plasmids similar in size to one of three previously described nonconjugative plasmids of molecular mass 4.9, 5.7, and 7.0 megadaltons (Mdal) (3,6,7). These plasmids are known not to carry the tetracycline resistance determinant.…”
Section: Methodsmentioning
confidence: 99%
“…Strains were screened for the presence of plasmids as described by Meyers et al (19) and previously reported (3,6). Plasmid DNA for restriction digestion was prepared by a modification (8) Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations